Local positioning system-derived external load of female and male varsity ice hockey players during regular season games - Gamble, A. S. D.; Bigg, J. L.; Nyman, D. L. E.; Spriet, L. L. (Frontiers in Physiology, 2022)
Purpose: The purposes of this study were to quantify the external load for female and male varsity ice hockey players during regular season games using a local positioning system (LPS), compare LPS-derived external load between sexes and positions, and compare skating distances in absolute and relative speed zones.